Deciphering the Clinical Presentations in LMNA-related Lipodystrophy: Report of 115 Cases and a Systematic Review - Özge Besci; Maria Cristina Foss‐Freitas; Natália Rossin Guidorizzi; Merve Çelik Güler; Donatella Gilio; Jessica N. Maung; Rebecca L. Schill; Keegan S. Hoose; Bonje Obua; ANABELA DILL GOMES; İlgın Yıldırım Şimşir; Korcan Demir; et al. (2023)
Lipodystrophy syndromes are a heterogeneous group of rare genetic or acquired disorders characterized by generalized or partial loss of adipose tissue. LMNA-related lipodystrophy syndromes are classified based on the severity and distribution of adipose tissue loss.